FROM THE HISTORY OF EARLY MEDIEVAL POTTERY CRAFT - Tuychiboev Bakhodir Bosimovich.; Rakhmonov Jonibek. (Scholar Express Journal, 2022)
In Ustrushona, one of the historical and cultural regions of Central Asia, pottery craft has been active since ancient times. In Ustrushona, ancient cities were studied, where potters' neighborhoods were recorded. The article analyzes pottery khumdons of ancient times found in Munchogtepa, Nurtepa, Qaliyatepa monuments of Ustrushona, city monuments such as Orda in Jizzakh, Kultepa in Zomin, Bunjikat, pottery khumdons of the middle ages and materials of potters' quarters. These finds really indicate that the pottery craft was developed in Ustrushona and had local characteristics.
Keywords: Archaeological complexes; handicrafts; pottery khumdons